Perceptions of secondary school management teams in managing pregnant learners in an urban context - Phindile P. Twala; Antoinette du Preez; Tinda Rabie (AOSIS, 2022)
Background: Teenage pregnancy is a complex issue globally, which is also a challenge in South Africa. Pregnant learners are allowed by the law to attend school for the whole duration of pregnancy. Although not medically trained or equipped to handle any emergencies, the school management teams are tasked to manage these learners by the Measures of the Prevention and Management of Learner Pregnancy Policy. Aim: This study aimed to determine the school management teams' perceptions of managing pregnant learners in urban secondary schools. Setting: This study was conducted in four secondary schools in Gauteng province, Soweto-Pimville District 10. Methods: This study employed a qualitative, descriptive design. Purposive sampling was carried out (n = 13), semi-structured WhatsApp video call interviews were conducted and Tesch's data analysis steps were utilised to analyse the data. Results: Five themes emerged: Theme 1: the role of school management teams in managing pregnant learners; Theme 2: challenges of unplanned deliveries at school; Theme 3: personal thoughts of educators on managing pregnant learners; Theme 4: skills training requirements for educators to manage pregnant learners; and Theme 5: coping mechanisms for school management teams. Conclusion: Collaboration between the department of health, department of education and the department of social development is essential in the management of pregnant learners at school. Contribution: Similar studies have been conducted in various rural areas of South Africa. Limited literature was found for urban areas; therefore, the researcher is of the opinion that the findings of this study could contribute to the body of knowledge.